The delta opioid receptor: an evolving target for the treatment of brain disorders - Pradhan, Amynah A (2011)
Compared to the better-known mu opioid receptor, delta opioid receptors have been relatively understudied. However, the development of highly selective delta opioid agonists, and the availability of genetic mouse models have extended our knowledge of delta opioid receptors in vivo. Here we review recent developments in the characterization of delta opioid receptor biology, and aspects of delta opioid receptor function that have potential for therapeutic targeting. Preclinical data have confirmed that delta opioid receptor activation reduces persistent pain and improves negative emotional states; clinical trials have been initiated to assess the effectiveness of delta opioid agonists in chronic pain and depression. Further, a possible role for these receptors in neuroprotection is being investigated. The usefulness of targeting delta opioid receptors in drug abuse remains open, and there is an emerging role of these receptors in impulse control disorders. Finally, the recent demonstration of biased agonism at the delta opioid receptor in vivo opens novel perspectives towards targeting specific therapeutic effects through drug design.